2015
DOI: 10.1016/j.neurobiolaging.2015.01.021
|View full text |Cite
|
Sign up to set email alerts
|

Cerebrospinal fluid tau levels are a marker for molecular subtype in sporadic Creutzfeldt-Jakob disease

Abstract: CitationCerebrospinal fluid tau levels are a marker for molecular subtype in sporadic Creutzfeldt-Jakob disease. 2015, 36 Abstract:The molecular subtype of sporadic Creutzfeldt-Jakob disease (sCJD) is an important prognostic marker for patient survival. However, subtype determination is not possible during life-time. Since the rate of disease progression is associated with the molecular subtype, this study aimed at investigating if total tau, a marker of neuronal death, allows pre-mortem diagnosis of molecul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
25
2
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
9
1

Relationship

3
7

Authors

Journals

citations
Cited by 34 publications
(35 citation statements)
references
References 12 publications
7
25
2
1
Order By: Relevance
“…On the contrary, the sensitivity of t-Tau towards sCJD remained unchanged by these patient characteristics. Despite the fact that the relatively small number of patients might limit the conclusions taken from this analysis, these are in general agreement with the results from large population studies [50,53]. This difference in the protein markers sensitivity between sCJD sub-types might be accounted by the modulation of clinical phenotype by molecular characteristics.…”
Section: Discussionsupporting
confidence: 86%
“…On the contrary, the sensitivity of t-Tau towards sCJD remained unchanged by these patient characteristics. Despite the fact that the relatively small number of patients might limit the conclusions taken from this analysis, these are in general agreement with the results from large population studies [50,53]. This difference in the protein markers sensitivity between sCJD sub-types might be accounted by the modulation of clinical phenotype by molecular characteristics.…”
Section: Discussionsupporting
confidence: 86%
“…For instance, we recently reported that CSF tau is a marker for the molecular type in sCJD, which might, among others, reflect different intensities of neuronal damage [19,20]. Differences of tau levels dependent on patient characteristics might have led to the heterogeneity in diagnostic accuracy measures reported for tau.…”
Section: Introductionmentioning
confidence: 99%
“…Total tau protein can be used as a diagnostic test for the assessment of PRNP when the codon 129 genotype is known (26), while the marker is not CJD-specific and can also be detected in numerous other diseases. Certain studies have shown that the sensitivity of 14-3-3 protein for detecting CJD varies for different CJD genotypes: From 57% in MV2 to 100% in MV1 and VV1 cases, with a specificity from 84 to 95% (27,28).…”
Section: Discussionmentioning
confidence: 99%